Prototype tests for the ALICE TRD - Andronic, Anton; Braun-Munzinger, Peter; Appelshäuser, Harald; Herrmann, Norbert; Stachel, Johanna; Wessels, Johannes P. (IEEE transactions on nuclear science, 2001)
A transition radiation detector (TRD) has been designed to improve the electron identification and trigger capability of the ALICE experiment at the Large Hadron Collider (LHC) at CERN. We present results from tests of a prototype of the TRD concerning pion rejection for different methods of analysis over a momentum range from 0.7 to 2 GeV/c. We investigate the performance of different radiator types, composed of foils, fibers and foams
Gesehen am 26.02.2018